Identification of tubulin isoforms in the plasmodium of Physarum polycephalum by in vitro microtubule assembly. - Roobol, A; Wilcox, M; Paul, E; Gull, K (1984)
The tubulins of the plasmodium of Physarum polycephalum have been identified by in vitro microtubule assembly from partially purified extracts of asynchronous microplasmodia and late G2 macroplasmodia. The plasmodial tubulin group comprised of 2 alpha tubulins (app. m.w. 51000 daltons) and 2 beta tubulins (app. m.w. 58000 daltons and 55000 daltons) and appeared to be identical with a group of polypeptides which are synthesized periodically in late G2. Two of the plasmodial tubulin subunits (one alpha and one beta) were identical to the Physarum amoebal tubulin alpha and beta subunits as characterised by 2D gel positions.